1981
DOI: 10.1128/jcm.14.2.210-221.1981
|View full text |Cite
|
Sign up to set email alerts
|

Improved detection of viruses by electron microscopy after direct ultracentrifuge preparation of specimens

Abstract: We have adapted the Beckman Airfuge air turbine ultracentrifuge and the new EM-90 particle-counting rotor to improve detection by electron microscopy of viruses in clinical specimens. Samples were clarified by centrifugation, pelleted in the EM-90 rotor directly to Formvar-coated copper grids, and stained with 1.5% sodium phosphotungstate. Virus counts and endpoint titrations of serial dilutions of partially purified preparations of poliovirus, SAIl rotavirus, herpes simplex

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
27
0

Year Published

1985
1985
2015
2015

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 64 publications
(29 citation statements)
references
References 11 publications
0
27
0
Order By: Relevance
“…By resuspending the pellet in a small volume, the virus is concentrated 50 -100fold. Alternatively, particles may be sedimented directly onto the grid using the Airfuge ® technique, resulting in similar enrichment factors (Gelderblom and Reupke, 1978;Hammond et al, 1981).…”
Section: Methods Used In Diagnostic Emmentioning
confidence: 99%
“…By resuspending the pellet in a small volume, the virus is concentrated 50 -100fold. Alternatively, particles may be sedimented directly onto the grid using the Airfuge ® technique, resulting in similar enrichment factors (Gelderblom and Reupke, 1978;Hammond et al, 1981).…”
Section: Methods Used In Diagnostic Emmentioning
confidence: 99%
“…The enrichment factor for poxviruses is similar to that given by other authors using the airfuge (Müller et al 1981;Biel and Gelderblom 1999a), although it is difficult to make direct comparisons because the airfuge parameters were not identical and, moreover, enrichment factors were not determined at the detection limit. Higher enrichment factors might be achieved using the particle counting EM-90 Beckman rotor (Hammond et al 1981) although a direct comparison of the two rotor systems, including a critical evaluation of practical handiness, has yet to be published. Differences between the detection limit of spores and virus using airfuge enrichment may be explained by their different sizes and therefore, different susceptibilities to the mechanical forces exerted on the particles.…”
Section: Discussionmentioning
confidence: 99%
“…All specimens were examined by negative-stain EM after concentration by direct ultracentrifugation (Hammond et al, 1981) and identified by specific morphology. An EIA rotavirus (Rotaclove, Cambridge Biosciences) was used on a seasonal basis from December to March.…”
Section: Electron Microscopymentioning
confidence: 99%
“…This study was undertaken to examine the individual adenovirus types from fecal specimens in children under 3 years of age in Manitoba, Canada, and to compare the methods of detection by virus culture (VC), EM with concentration by direct ultracentrifugation (Hammond et al, 1981), and EIA (Cambridge Bioscience). During July 1990-1991, 1187 fecal samples from children K3 years of age were collected at clinics and hospitals and submitted to the Cadham Provincial Laboratory, Winnipeg, Manitoba, Canada, for the diagnosis of virus infection.…”
Section: Introductionmentioning
confidence: 99%